Aza follow-ups to BI 207524, a thumb pocket 1 HCV NS5B polymerase inhibitor. Part 1: Mitigating the genotoxic liability of an aniline metabolite. Issue 5 (1st March 2015) - Beaulieu, Pierre L.; Bolger, Gordon; Duplessis, Martin; Gagnon, Alexandre; Garneau, Michel; Stammers, Timothy; Kukolj, George; Duan, Jianmin
Graphical abstract